Severe Combined Dyslipidemia With a Complex Genetic Basis - Ryan Le MD; Minan Abbas MB ChB, FRCPC; Adam D. McIntyre BSc; Robert A. Hegele MD, FRCPC, FACP (SAGE Publishing, 2019)
Background. Familial dysbetalipoproteinemia (also known as type 3 hyperlipoproteinemia) is typically associated with homozygosity for the apolipoprotein E2 isoform, but also sometimes with dominant rare missense variants in the APOE gene. Patients present with roughly equimolar elevations of cholesterol and triglyceride (TG) due to pathologic accumulation of remnant lipoprotein particles. Clinical features include tuberoeruptive xanthomas, palmar xanthomas, and premature vascular disease. Case. A 48-year-old male presented with severe combined dyslipidemia: total cholesterol and TG were 11.5 and 21.4 mmol/L, respectively. He had dyslipidemia since his early 20s, with tuberous xanthomas on his elbows and knees. His body mass index was 42 kg/m 2 . He also had treated hypertension, mild renal impairment, and a history of gout. He had no history of cardiovascular disease, peripheral arterial disease, or pancreatitis. Multiple medications had been advised including rosuvastatin, ezetimibe, fenofibrate, and alirocumab, but his lipid levels were never adequately controlled. Genetic Analysis. Targeted next-generation sequencing identified (1) the APOE E2/E2 homozygous genotype classically described with familial dysbetalipoproteinemia; (2) in addition, one APOE E2 allele contained the rare heterozygous missense variant p.G145D, previously termed apo E-Bethesda; (3) a rare heterozygous APOC2 nonsense variant p.Q92X; and (4) a high polygenic risk score for TG levels (16 out of 28 TG-raising alleles) at the 82nd percentile for age and sex. Conclusion. The multiple genetic "hits" on top of the classical APOE E2/E2 genotype likely explain the more severe dyslipidemia and refractory clinical phenotype.